1995
DOI: 10.1073/pnas.92.18.8348
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of p53 in senescing fibroblasts.

Abstract: The p53 tumor-suppressor protein binds DNA and activates the expression of a 21-kDa protein that inhibits both the activity of cyclin-dependent kinases and the function of proliferating cell nuclear antigen. Since p21 expression has been reported to increase 10-to 20-fold as human diploid fibroblasts lose the ability to replicate, we examined the expression and activity of p53 during replicative aging. Similar levels of total p53 mRNA and protein were expressed in low-passage (young) and high-passage (old) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
192
4
4

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(215 citation statements)
references
References 43 publications
15
192
4
4
Order By: Relevance
“…Several groups have demonstrated that senescent cells arrest with a G1 DNA content, and express increased levels of p16, p21 and p53 (Hara et al, 1996;Alcorta et al, 1996;Rezniko et al, 1996;Atadja et al, 1995;Serrano et al, 1997). p16 accumulates both in ®broblasts and uroepithelial cells as a consequence of the increasing number of population doublings, eventually leading to senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that senescent cells arrest with a G1 DNA content, and express increased levels of p16, p21 and p53 (Hara et al, 1996;Alcorta et al, 1996;Rezniko et al, 1996;Atadja et al, 1995;Serrano et al, 1997). p16 accumulates both in ®broblasts and uroepithelial cells as a consequence of the increasing number of population doublings, eventually leading to senescence.…”
Section: Discussionmentioning
confidence: 99%
“…We also performed p53 dependent reporter assays in NIH 3T3 and NIH 3T3/mot-2 cells. The activity of the full length p21 WAF1 promoter reporter plasmid was three-five fold high in NIH 3T3 cells in different experiments [22], [25] and data not shown]. This suggested that the high level of p21 WAF1 transcript in NIH 3T3/mot-2 cells is either regulated by elements located further upstream to the 2501 bp in the promoter used in the reporter plasmid or by post-transcriptional mechanism(s).…”
Section: Nih 3t3/mot-2 Cells Show An Upregulation Of P21waf1 Expressionmentioning
confidence: 90%
“…This was contrary to the inactivation of p53 function by mot-2 [22], [25]. We first ascertained that the band detected on Western blot was indeed p21 WAF1 by using serially passaged normal mouse embryonic fibroblasts (CMEF) and NIH 3T3 cells cultured at different density ( Fig 1A).…”
Section: Nih 3t3/mot-2 Cells Show An Upregulation Of P21waf1 Expressionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, many other functions have also been reported including roles in differentiation 119 and senescence. 120 Alternatively, normal p53 may suppress inappropriate angiogenesis through transcriptional regulation of fibroblast growth factor (FGF-2), 121 thrombospondin 122 and vascular endothelial growth factor. 122,123 Normal p53 protein has a very short half-life within cells, whereas mutated p53 protein commonly has a prolonged half-life and is detectable by immunohistochemistry.…”
Section: P53 Tsgmentioning
confidence: 99%